Isolation of phytoplasmas associated to frogskin disease in cassava - Betancourth, Carlos; Pardo, Juan Manuel; Muñoz, Jaime E.; Álvarez, Elizabeth (Universidad de Ciencias Aplicadas Y Ambientales - UDCA, 2019)
Frogskin is the most limiting disease of cassava crops in Colombia, causing losses in production up to 90%. Since this disease was associatated with 16SrIII phytoplasma presence, a study was carried out to isolate this phytoplasma using liquid and solid culture media. Root, petiol, stem, leaf and cutting tissues of cassava affected by frogsking were employed as source materials. Molecular and microscopy techniques were applied to verify the phytoplasma growth and to discard other microorganism ́s presence. The results showed that the media consistently allow phytoplasma growth, and colonies in solid medium were obtained. PCR, qPCR and sequencing tests confi rmed the presence of 16SrIII group phytoplasmas in both liquid and solid culture media. Additionally, the isolation of a pigeon pea witches' broom phytoplasma strain (group 16SrIX) was obtained from stems, petioles and fl owers of symptomatic Catharanthus roseus confi rming the effectiveness of the medium in the phytoplasma isolation and culture. This is the fi rst isolation of fi eld-collected phytoplasma strains in groups 16SrIII and 16SrIX in America that confi rm and corroborate the previous results in phytoplasma cultivation achieved on micropropagated and fi eld-collected phytoplasma infected samples.